2023
DOI: 10.1002/pad.2026
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking ‘public silence’: Civil society activism under authoritarian rule in Ethiopia

Camille Louise Pellerin

Abstract: How do civil society organisations (CSOs) and the state interact in non‐democratic settings? Non‐democratic regimes often meet civil society activism with repression, however, on an every‐day basis contestation and control take more diverse forms. To capture how CSOs bargain with and contest state power, as well as how states police CSOs, this article draws on the case of Ethiopia (1991–2018). It analyses different types of interactions between service providing CSOs and state actors and studies when and how C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…For example, Pellerin (2023) conducted 48 interviews with civil society activists, civil servants, and other experts in Ethiopia and found that civil society organizations filled gaps where the government was unable to reach simultaneously making these regimes more stable. In this context, the government would co-opt these organizations and, in some cases, cooperate with them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Pellerin (2023) conducted 48 interviews with civil society activists, civil servants, and other experts in Ethiopia and found that civil society organizations filled gaps where the government was unable to reach simultaneously making these regimes more stable. In this context, the government would co-opt these organizations and, in some cases, cooperate with them.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the literature focuses on China and Turkey (Bakir & Gunduz, 2019). Other studies have focused on India, Pakistan, and Bangladesh in South Asia (Palmer, 2006), and Ghana and Ethiopia in Africa (Kumi, 2022;Pellerin, 2023). However, Indonesia has been engaged in this sector.…”
Section: Introductionmentioning
confidence: 99%